Manajemen Hipertensi pada Layanan Primer: Studi Kualitatif - Muliyadi; Prahardian Putri; Faiza Yuniati; Jawiyah; Sri Yulia (Journal of Bionursing, 2023)
Background. the prevalence of hypertension is currently increasing and primary care is the main service in the prevention and management of hypertension. This study aims to obtain an overview of the management of hypertension non-communicable diseases (PTM) in primary care. Methods. Qualitative descriptive research with participants 13 health workers consisting of 12 nurses and 1 midwife, the program responsible for non-communicable diseases (PTM) of the health office and the Puskesmas in Palembang City. Data collection was carried out through Focus Group Discussions with discussion guide instruments. Thematic analysis is carried out on information presented in a narrative manner that describes themes, categories and keywords. Results. the study obtained five themes, namely the health problems of hypertensive patients with physical, psychosocial and social categories; the form of hypertension PTM building services with the category of services in the health center and services outside the building; information needs of Hypertension patients with information categories of signs and symptoms of hypertension, treatment, care; program implementation support in the categories of policy, community participation, government, patient groups and families and obstacles to program implementation in the category of low awareness of hypertension patients, lack of participation of cadres, limited resources (HR), program achievement targets that are difficult to realize Conclusion. the research program managing non-communicable diseases Hypertension in primary care have been implemented, although there are obstacles in achieving the program.